Assessment of learning in Interprofessional Education in Health Higher Education: protocol for an integrative literature review on pedagogical approaches - Moraes, Rafael Silvério de; Souza, Camila Mendes da Silva; Leonello, Valéria Marli (O Mundo da Saúde, 2025)
Interprofessional Education (IPE) is defined as situations in which professionals or students from two or more different fields learn with and about each other, with the aim of improving collaboration and the quality of healthcare services provided. When introducing IPE into teaching experiences, it is also necessary to address the assessment of learning within this process. One of the critical issues in assessing learning in IPE is the pedagogical approach adopted by the educational program. In general, such approaches are either not explicitly stated or, when they are, are not reflected in the proposed assessment methods. The objective of this study is to identify and analyze, through an Integrative Literature Review (ILR), the pedagogical approaches used in the assessment of learning in IPE experiences in Health Higher Education. The ILR is a methodology that allows for the rigorous identification and synthetic evaluation of studies available on the topic under investigation. The review question for this study was developed using the strategy that includes Population, Interest, and Context. The ILR methodology will follow six steps: formulation of the research question, definition of inclusion and exclusion criteria, data collection and literature search strategies, rigorous evaluation of the selected studies, analysis and synthesis of the findings, and presentation and interpretation of the results. This ILR aims to identify the predominance of traditional assessments that limit interprofessional learning and to emphasize the importance of integrating formative and summative assessment methods into the teaching process. The description of pedagogical approaches in this ILR may contribute to the development of effective assessment practices in IPE, guiding educators and academic administrators. The results are expected to promote more effective pedagogical policies aligned with the demands of Health Higher Education.